Does Pectoralis Minor Stretching Provide Additional Benefit over an Exercise Program in Participants with Subacromial Pain Syndrome? a Randomized Controlled Trial - Rios-Riquelme, M (Elsevier Ltd, 2019)
Background: Adaptive shortening of the pectoralis minor is one of the biomechanical mechanisms associated with subacromial pain syndrome (SPS). Objective: To compare the effects of an exercise program alone with an exercise program in combination with pectoralis minor stretching in participants with SPS. Design: Randomized controlled trial. Methods: Eighty adult participants with SPS were randomly allocated to two groups. The control group (n = 40) received a 12-week specific exercise program and the intervention group (n = 40) received the same program plus stretching exercises of the pectoralis minor muscle. The primary outcome measure was shoulder function assessed by a Constant−Murley questionnaire, and the secondary outcomes were the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, visual analog scale (VAS), and pectoralis minor resting length. Results: The present study shows no difference between the two interventions according to the Constant−Murley questionnaire (1.5 points; p = 0.58), VAS at rest (0.2 cm; p = 0.11), VAS at movement (0.5 cm; p = 0.08), and pectoralis minor resting length (0.3 cm; p = 0.06). The DASH questionnaire showed greater functional improvement in the control group (5.4 points; p = 0.02). Finally, only pectoralis minor length index showed difference statistical significant in favor of intervention group (0.3%; p = 0.04). Conclusion: In the short-term, the addition of a program of stretching exercises of the pectoralis minor does not provide significant clinical benefit with respect to functional improvement or pain reduction in participants with SPS. Trial registration: Brazilian registry of clinical trials UTN number U1111-1210-3555. Registered 5 March 2018. © 2019 Elsevier Ltd